History of colombian education: A genealogical-archaeological analysis of the configuration of the subjects (teachers and students) - Leonardo Alberto Mauris De la Ossa (Corporacion Universitaria Rafael Nuñez, 2022)
The history of education has been the scene of struggles and power games that pursue the configuration and delimitation of what should be understood by the subjectivity of teachers and students: in all cases, in order to legitimize economic, political, religious and philosophical structures. In this regard, the country's public education system has been a powerful corrective and disciplinary instrument to mold the citizen desired by the structure. However, a purely historiographic study to determine the ups and downs of the main events, names, decrees and institutions that were forging what is now known as the Colombian education system is not enough to understand the discourses that established the boundaries of what should or should not be accepted as the role of the teacher and the student. That is why this study followed the methodological guidelines of the archaeological-genealogical research of the French philosopher Michel Foucault. In this context, it is mentioned as results, firstly, that the formation of boys and girls, in its genesis, was given by the need to give a soul to the newly discovered Indian; therefore, the first instructor was the doctrinal priest whose functions consisted of teaching both the language to the barbarian; like catechesis to man without God. Secondly, the following transformations that public instruction underwent had as their object the service of governmentality. Either to consolidate the colony, or to propagandize the republic; The aim was always to train the body and consciences of the citizens. Thus, the resignification of the purposes of education must begin by establishing epistemological bases that redesign the role of teachers and students.